Comparison of Drainage Methods After Pyeloplasty in Children: A 14-Year Study - Kong, Xiangpan; Li, Zhenpeng; Li, Mujie; Liu, Xing; He, Dawei (Frontiers in Pediatrics, 2021)
Objective: To verify the safety of laparoscopic pyeloplasty (LP) in young children (below 1 years) and summarize our experiences about drainage stent with 14-year study. Methods: We reviewed the data of the 937 children operated on for hydronephrosis due to congenital ureteropelvic junction obstruction (UPJO) between July 2007 to July 2020. Patients’ demographics, perioperative details, postoperative drainage stents, complications, hospital stay, and long-term follow-up outcomes were analyzed. Long term follow-up was performed by ultrasound at 3,6 months and 1,2 years post-operatively, other imaging examinations would be added if necessary. Moreover, we reviewed the details of 9 cases of recurrence after laparoscopic pyeloplasty. Results: In the young children of LP and OP group, results showed that there were statistical differences between the two groups in terms of operation time, blood loss, and length of hospital stay(p<0.01), no statistical differences in the incidence of postoperative complications and long-term follow-up results at the same time (p>0.05). Statistical differences were found in the incidence of postoperative complications from the three postoperative drainage stent groups, especially the incidence of reoperations (p<0.01)，there were 6 cases(3.19%)recurrences in TEUS group, 2 cases(0.36%) in DJ group, and 1 case(0.93%) in PU group. In the 6 recurrent cases from TEUS group, 4 cases (44.4%) were found to have stenosis, and 2 cases (22.2%) had iatrogenic valvular formation. Conclusions: LP in young children is feasible and safe. But not all 3 drainage stents are suitable for pelvic urine drainage after laparoscopic pyeloplasty. The use of the TEUS should be carefully select.